Sustainable Dryland Smallholder Farming in Sub-Saharan Africa - Twomlow, Steve; Riches, Charlie; O'Neil, Dave; Brookes, Phil; Ellis-Jones, Jim (Annals of Arid Zone, 2016)
The African smallholder farmer faces a bleak future unless some basic trends can be reversed. While the West seems to be moving philosophically "towards more organically based low input agricultural systems, we suggest that if Africa adopts similar policies, the results will be an even bigger disaster than is currently the case. What is clear from this review is that there is no single method of soil and water management that will fit all circumstances to achieve sustainable agricultural production at the small holder level in sub-Saharan Africa. Each technology/option has advantages and limitations, depending on the biophysical (soil and rainfall) resources, crops grown, availability of crop residues and manures, farmer resources, and farmers' diverse and complex criteria for decision making. However, significant increases in crop yields will only occur when improved conservation practices, like conservation tillage, are combined with improved soil fertility management (both organic and inorganic), and effective weed management. The more recent research "results also indicate that the performance of soil and water management , technologies is highly dependent, not only on an extreme variability of the soil's natural potential, but even more on the management capacity of farmers themselves. Unless smallholder farmers themselves help develop the understanding and skills required to manage their land in a way, which combines production and conservation, the potential impact of all this ,knowledge and research will remain unfulfilled. This insight sets the stage for the future focus of research and extension into sustainable agriculture, not only in southern Africa, but in all developing areas of the world.